A bifunctional catalase‐peroxidase, MakatG1, contributes to virulence of Metarhizium acridum by overcoming oxidative stress on the host insect cuticle. (13th October 2017) - Li, Guohong; Fan, Anni; Peng, Guoxiong; Keyhani, Nemat O.; Xin, Jiankang; Cao, Yueqing; Xia, Yuxian
Summary: Microbial pathogens are exposed to damaging reactive oxygen species (ROS) produced from a variety of sources including chemical reactions due to exposure to stress (UV, heat) or by hosts as a defense response. Here, we demonstrate that a bifunctional catalase‐peroxidase, MakatG1, in the locust‐specific fungal pathogen, Metarhizium acridum, functions as a ROS detoxification mechanism during host cuticle penetration. MakatG1 expression was highly induced during on‐cuticle appressoria development as compared to vegetative (mycelia) growth or during in vivo growth in the insect hemocoel. A MakatG1 deletion mutant strain ( ΔMakatG1 ) showed decreased catalase and peroxidase activities and significantly increased susceptibility to oxidative (H2 O2 and menadione) and UV stress as compared to wild‐type and complemented strains. Insect bioassays revealed significantly reduced virulence of the ΔMakatG1 mutant when topically inoculated, but no impairment when the insect cuticle was bypassed. Germination and appressoria formation rates for the ΔMakatG1 mutant were decreased on locust wings and quinone/phenolic compounds derived from locust wings, but were not affected on plastic surfaces compared with the wild‐type strain. These data indicate that MakatG1 plays a pivotal role in penetration, reacting to and detoxifying specific cuticular compounds present on the host cuticle during the early stages of fungal infection.